Revisão taxonômica do grupo Hyphessobrycon panamensis Durbin (Characiformes: Characidae). - Ota, Renata Rúbia (2018)
A revision of the Hyphessobrycon panamensis species group was carried out, recognizing 15 valid species of the 21 nominal, and two new species. Among the valid species of Central America: H. panamensis restricted to the drainages of Atlantic and Pacific coasts of Panama; H. savagei distributed in the río Pírris and río Térraba basins, Pacific coast of Costa Rica; H. tortuguerae in the río Frio and río Tortuguero basins, Costa Rica, río San Juan basin and Nicaragua Lake, borderline of Costa Rica and Nicaragua, and the río Plátano basin, Honduras; and Hyphessobrycon sp. 1 described from the río Sixaola and río Tortuguero basins, Atantic coast of Costa Rica. Among the trans-andean South America: H. columbianus distributed on the río Acandi basin, Colombia; H. condotensis in the río Atrato, río Baudó, lower río Magdalena and río San Juan basins, Colombia, and with H. sebastiani as junior-synonym; H. daguae, erected to specific level and with H. chocoensis as junior-synonym, distributed in the río Dagua, río Patía and río Telembí basins, Colombia, and widened to the río Mira basin, borderline of Colombia and Ecuador, río Cayapas, río Mataje and río Santiago basins, Northern Ecuador; H. ecuadoriensis distributed on the río Guayas basin, Southern Ecuador and with Megalamphodus ecuadorensis (=H. ecuadorensis) as junior-synonym. Among the cis-andean South America: H. bifasciatus in coastal drainages from Southern Bahia to Northern Santa Catarina, upper rio Iguaçu, upper rio Paranapanema and upper rio Tietê; H. flammeus in coastal drainages of Rio de Janeiro and upper rio Tietê; H. griemi in the upper rio Iguaçu, rio Tibagi and coastal drainages from São Paulo to Rio Grande do Sul; H. igneus in the Laguna dos Patos system and río Uruguay basin, Brazil and Uruguay; H. itaparicensis in coastal drainages from Southern Sergipe to Bahia, H. weitzmanorum in streams of the upper rio Araguaia; and Hyphessobrycon sp. 2 only known from the Parque Municipal do Iguaçu. Additionally, key for identification, map of geographical distribution and pictures of all species are provided.